2022
DOI: 10.1021/acs.jpcb.2c04397
|View full text |Cite
|
Sign up to set email alerts
|

Beyond “Mega”: Origin of the “Giga” Stokes Shift for Triazolopyridiniums

Abstract: Over the past decade, fluorophores that exhibit "mega" Stokes shifts, defined to be Stokes shifts of greater than 100 nm, have gained considerable attention due to their potential technological applications. A subset of these fluorophores have Stokes shifts of at least 10,000 cm −1 , for whom we suggest the moniker "giga" Stokes shift. The majority of "giga" Stokes shifts reported in the literature arise from the twisted intramolecular charge transfer mechanism, but this mechanism does not fit empirical charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
0
4
0
2
Order By: Relevance
“…Figure 4A outlines a brief comparison of Stokes shifts of representative PyrAtes (bottom) with selected known fluorophores (top). [28,29,[49][50][51][52][53][54][55][56][57][58] Change at the ground-and excited-state energy profiles of certain fluorescent probes in response to environment (e.g., solvent [59][60][61] or pH [62] ) has been an attractive means in proteomics for the study of protein-protein interactions (PPIs) or protein folding, [63] as well as in the study of lipid dynamics of cellular membranes, for diagnostics in medicine, [62,64] and for selective organelle imaging. [65] As a canonical probe, we examined the solvatochromic behavior of PyrAte 7 a (Figure 4B).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 4A outlines a brief comparison of Stokes shifts of representative PyrAtes (bottom) with selected known fluorophores (top). [28,29,[49][50][51][52][53][54][55][56][57][58] Change at the ground-and excited-state energy profiles of certain fluorescent probes in response to environment (e.g., solvent [59][60][61] or pH [62] ) has been an attractive means in proteomics for the study of protein-protein interactions (PPIs) or protein folding, [63] as well as in the study of lipid dynamics of cellular membranes, for diagnostics in medicine, [62,64] and for selective organelle imaging. [65] As a canonical probe, we examined the solvatochromic behavior of PyrAte 7 a (Figure 4B).…”
Section: Methodsmentioning
confidence: 99%
“…One of the most significant findings of this study is that the synthesis of PyrAtes is a straightforward process and delivers fluorophores with large Stokes shifts (typically >135 nm). Figure 4A outlines a brief comparison of Stokes shifts of representative PyrAtes (bottom) with selected known fluorophores (top) [28,29,49–58] …”
Section: Figurementioning
confidence: 99%
“…Eine der wichtigsten Erkenntnisse aus dieser Studie ist, dass die Synthese von PyrAt‐Verbindungen ein unkomplizierter Prozess ist und Fluorophore mit großen Stokes‐Verschiebungen (typischerweise >135 nm) liefert. Abbildung 4A zeigt einen kurzen Vergleich der Stokes‐Verschiebungen von repräsentativen PyrAt‐Verbindungen (unten) mit ausgewählten, literaturbekannten Fluorophoren (oben) [28,29,49–58] …”
Section: Figureunclassified
“…Abbildung 4A zeigt einen kurzen Vergleich der Stokes-Verschiebungen von repräsentativen PyrAt-Verbindungen (unten) mit ausgewählten, literaturbekannten Fluorophoren (oben). [28,29,[49][50][51][52][53][54][55][56][57][58] Die Änderung des Energieprofils im Grundzustand und im angeregten Zustand bestimmter fluoreszierender Sonden als Reaktion auf die Umgebung (z. B. Lösungsmittel [59][60][61] oder pH-Wert [62] ) ist ein attraktives Mittel in der Proteomik zur Untersuchung von Protein-Protein-Wechselwirkungen (PPIs) oder der Proteinfaltung, [63] sowie zur Untersuchung der Lipiddynamik zellulärer Membranen, zur Diagnostik in der Medizin, [62,64] oder zur selektiven Darstellung von Organellen.…”
unclassified
“…In particular, small organic fluorophores with a donor-acceptor (D-A) architecture have received considerable interest due to their distinct and highly tunable optical properties. [1][2][3][4] Much effort has been made to design and synthesize new D-A organic fluorophores by changing the types of donor and acceptor. [5][6][7][8] These reported studies showed that changing the nature of the donor and acceptor would affect the properties of D-A organic fluorophores.…”
Section: Introductionmentioning
confidence: 99%